Pendampingan Implementasi Website Sistem Informasi PHBS Rumah Tangga untuk Meningkatkan Efektivitas Pengelolaan Data - Aryanti, Utami; Anwar, Moh. Taufan; Dewi, Sofia; Naasyiah, Rifdah (Ma'soem University, 2025)
Clean and Healthy Living Behavior (PHBS) is an important indicator in improving public health. However, the process of collecting data and fostering PHBS in households in the Cicalengka DTP Community Health Center (Puskesmas) is still done manually, often causing obstacles in data management and reporting. This community service activity aims to assist the Puskesmas in digitizing the process of collecting data and fostering PHBS through the creation of a information system website. The implementation method includes needs analysis, system design, implementation, user training, and field evaluation. The results of the activity indicate that the developed website can facilitate officers in collecting household data, monitoring PHBS indicators, and providing more structured guidance. In addition, the training activity increases officers' understanding of the use of information technology to support public health programs.